2020
DOI: 10.2460/ajvr.81.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of vatinoxan on somatic and visceral antinociceptive efficacy of medetomidine in dogs

Abstract: OBJECTIVETo determine whether concurrent vatinoxan administration affects the antinociceptive efficacy of medetomidine in dogs at doses that provide circulating dexmedetomidine concentrations similar to those produced by medetomidine alone. ANIMALS 8 healthy Beagles. PROCEDURESDogs received 3 IV treatments in a randomized crossover-design trial with a 2-week washout period between experiments (medetomidine [20 µg/ kg], medetomidine [20 µg/kg] and vatinoxan [400 µg/kg], and medetomidine [40 µg/kg] and vatinoxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Effects of dexmedetomidine, with or without vatinoxan, on the minimum alveolar concentration of isoflurane (MAC) in cats, have been investigated by Pypendop et al (2019a) and they advocated that vatinoxan increases the MAC of isoflurane in cats along with diminishing the potency of dexmedetomidine in reducing MAC. Huuskonen et al (2020) researched concerning the effect of simultaneous administration of vatinoxan on the antinociceptive efficacy of medetomidine in dogs, at doses providing circulating dexmedetomidine concentration equivalent to those produced by medetomidine alone. This randomized crossover study was performed in eight healthy beagle dogs, each receiving 3 intravenous treatment: medetomidine (20 μg/kg), medetomidine (20 μg/kg) with vatinoxan (400 μg/kg) and medetomidine (40 μg/kg) with vatinoxan (800 μg/kg), respectively and the sedation score, visceral and somatic nociception and the plasma drug concentration were assessed.…”
Section: Pharmacokinetic Effectsmentioning
confidence: 99%
“…Effects of dexmedetomidine, with or without vatinoxan, on the minimum alveolar concentration of isoflurane (MAC) in cats, have been investigated by Pypendop et al (2019a) and they advocated that vatinoxan increases the MAC of isoflurane in cats along with diminishing the potency of dexmedetomidine in reducing MAC. Huuskonen et al (2020) researched concerning the effect of simultaneous administration of vatinoxan on the antinociceptive efficacy of medetomidine in dogs, at doses providing circulating dexmedetomidine concentration equivalent to those produced by medetomidine alone. This randomized crossover study was performed in eight healthy beagle dogs, each receiving 3 intravenous treatment: medetomidine (20 μg/kg), medetomidine (20 μg/kg) with vatinoxan (400 μg/kg) and medetomidine (40 μg/kg) with vatinoxan (800 μg/kg), respectively and the sedation score, visceral and somatic nociception and the plasma drug concentration were assessed.…”
Section: Pharmacokinetic Effectsmentioning
confidence: 99%
“…This concept has been well‐documented in various species (Honkavaara et al, 2011; Restitutti et al, 2012; Rolfe et al, 2012; Sainmaa et al, 2019; Siao et al, 2017; de Vires et al, 2016), including sheep (Adam, Huuskonen, et al, 2018; Adam, Raekallio, Keskitalo, et al, 2018; Adam, Raekallio, Salla, et al, 2018; Bryant et al, 1998; Raekallio et al, 2010). Moreover, vatinoxan has no appreciable impact on agonist‐induced sedation in many species (Adam, Raekallio, Keskitalo, et al, 2018; Adam, Raekallio, Salla, et al, 2018; Honkavaara Pypendop et al, 2017; Honkavaara et al, 2008, 2017; Raekallio et al, 2010; Restitutti et al, 2011; Siao et al, 2017; Tapio et al, 2018; Vainionpää et al, 2013; de Vries et al, 2016), nor has it shown antinociceptive effects when the agonist concentration is similar in plasma (Huuskonen et al, 2020). Recently, we demonstrated in sheep that premedication with vatinoxan alleviated dexmedetomidine‐induced bronchoconstriction and hypoxaemia, and prevented the opacity detected by computer tomography (CT) in the ventrolateral parts of lungs (Adam, Huuskonen, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%